2002
DOI: 10.1558/jmea.v15i1.101
|View full text |Cite
|
Sign up to set email alerts
|

Social and Political Organisation on Crete in the Proto-palatial Period

Abstract: The model of the Minoan palace as a centralised political, economic and ideological authority, and of Minoan society as a hierarchical power structure, has to a large extent guided discussion of social complexity in the Middle Bronze Age on Crete. This paper draws attention to alternative models of power in which more agent-centred perspectives, such as heterarchy and factionalism, are preferred. On the basis of a case-study of the proto-palatial town of Malia (Crete), it is argued that these alternative model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 0 publications
1
42
0
Order By: Relevance
“…At the same time, the discovery of three of the ceremonial (large, thin) Double‐Axes – made of a material that is prone to disappearing from settlements – in the relatively humble settlements of the Mirabello Bay region may suggest that this group or class was not narrow and confined to the top of a conceptual Minoan hierarchy but was more broad‐based. This may coincide with some recent discussions of Minoan society which emphasize the apparent complexity in the evidence for social structure through the use of the terms ‘heterarchy’ and ‘factionalism’ (Melas 1995; Hamilakis 1997–8; Schoep 2002a; 2002b; Hamilakis 2002). The understanding of the Double‐Axe as a symbol of a social group would be compatible with the occurrences of the symbol in art and in the wider material record, while suggesting that as a votive its symbolism was as much to do with the dedicator as with the cult 16…”
Section: Discussionsupporting
confidence: 82%
“…At the same time, the discovery of three of the ceremonial (large, thin) Double‐Axes – made of a material that is prone to disappearing from settlements – in the relatively humble settlements of the Mirabello Bay region may suggest that this group or class was not narrow and confined to the top of a conceptual Minoan hierarchy but was more broad‐based. This may coincide with some recent discussions of Minoan society which emphasize the apparent complexity in the evidence for social structure through the use of the terms ‘heterarchy’ and ‘factionalism’ (Melas 1995; Hamilakis 1997–8; Schoep 2002a; 2002b; Hamilakis 2002). The understanding of the Double‐Axe as a symbol of a social group would be compatible with the occurrences of the symbol in art and in the wider material record, while suggesting that as a votive its symbolism was as much to do with the dedicator as with the cult 16…”
Section: Discussionsupporting
confidence: 82%
“…The organization of the western part of the West Wing suggests such rooms were devoted to storage. Scholars have warned that the Protopalatial palaces are still too often understood by climbing the chronological ladder upwards and considering these early complexes along the lines of their Neopalatial – or even Final Palatial – successors (Schoep , 102; , 39, n. 27). However, the present study has shown that a West Wing made of long, narrow storage rooms, sometimes associated with ritual spaces bordering the Central Court, is already a feature of the earliest complexes (Graham , 129; Macdonald , 42), a conclusion which has bearings on the socio‐political background of the First Palaces.…”
Section: Resultsmentioning
confidence: 99%
“…Arguments have also been brought forward to deny Near Eastern comparisons within Evans’ palace‐temple model, further questioning the traditional interpretation of the Minoan palaces (e.g. Farnoux ; ; Driessen ; Hamilakis ; Schoep ; ; ; Papadopoulos ). This revision has gone as far as questioning the conventional labelling of these complexes, favouring the less loaded term – though surely a less colourful one – of ‘court‐centered’ or ‘court building’ rather than ‘palace’, although in this paper the conventional term is maintained for descriptive reasons (Driessen ; Schoep , esp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…She demonstrates that the first (Protopalatial) palaces lack many ''palatial'' architectural features, which are instead found first in elite, nonpalatial structures in those same settlements (Schoep 2002b(Schoep , 2004(Schoep , 2006. Furthermore, elite pottery styles such as polychrome-painted Kamares ware, once believed to have been produced and consumed restrictively by palace elites at Knossos, are now known to have been imported and consumed in a wide range of palatial and nonpalatial locations on the site (Day and Wilson 1998).…”
Section: The Palaces Of Minoan Cretementioning
confidence: 99%